Philippine banking almanac, 1995 (Venture Unlimited, 1995)
An impressive encyclopedia of information on Philippine banks and financial institutions and related information. It provides useful reference and guide in determining which type of financial intermediary would best serve the needs of businessmen and entrepreneurs.